Procedural Ease, Interest Rates, and Trust as Drivers of Credit Decision-Making, Evidence from Bank BRI Customers in Bawean Island - Pahrudin, Pahrudin; Rosyid, Amrun; Goeyardi, Gema Merdeka (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyze the influence of perceived procedural ease, interest rates, and trust on the decision-making process of Bank BRI customers in Pulau Bawean when applying for credit. The research addresses gaps in prior studies by integrating these three variables simultaneously in the context of a remote island community. Design/methodology/approach: A quantitative approach was employed using survey data collected from BRI customers in Bawean Island who have taken credit. The study applied descriptive analysis, validity and reliability testing, and multiple linear regression to examine the relationships among variables. Findings: The results indicate that perceived procedural ease, interest rates, and trust each have a significant effect on credit decision-making. Furthermore, these variables collectively exert a strong influence on customers’ willingness to take credit Research limitations/implications: The study is limited to BRI customers in Pulau Bawean and focuses only on three independent variables, excluding other potential factors such as promotion, service quality, or income levels. Practical implications: Findings provide insights for Bank BRI to simplify procedures, set competitive interest rates, and strengthen customer trust, thereby enhancing credit uptake in remote regions. Originality/value: This research contributes by integrating operational, economic, and psychological factors into one model, specifically within the unique context of a geographically isolated island community, which has been underexplored in prior studies. Paper type: Research paper